L´interrégionalisme ASEAN-MERCOSUR: Relations diplomatiques et économiques - Fernandez Guillen, Oscar Eduardo (2024)
This chapter offers a study on comparative regionalism analysing the Association of Southeast Asian Nations (ASEAN) and the Southern Common Market (MERCOSUR) as integration processes with some proximities and common characteristics. Even with geographical, historical, and cultural distances, different origins, functioning, and results, the 21st century shows a growth in their economic interdependence at the trade level. Through empirical research supported by documentary compilation techniques and statistical data, the chapter describes the diplomatic rapprochement process between both sub-regions, the formalisation state of the ASEAN-MERCOSUR inter-regional relations, and their economic interactions in trade and investment during the period 2000-2022. It concludes that there are reasons to relaunch and deepen the inter-regionalism based on the consolidation of the ASEAN-MERCOSUR Dialogue Society, indefinite and on stand-by since the 1990s, which also could be an opportunity to begin the construction of a South American position towards the Indo-Pacific without polarisation between the United States and China.